Bioconversion of food waste by Chrysomya megacephala (Diptera: Calliphoridae) larvae: Potential for sustainable waste management and antimicrobial applications - Pluemkamon Phuwanatsarunya; Nophawan Bunchu; Worasak Kaewkong; Tongjit Thanchomnang; Ketsarin Thipphet; Sophit Khanthawong (PLoS ONE, 2025)
Addressing global food waste requires innovative and sustainable solutions. This study investigates the potential of Chrysomya megacephala (Diptera: Calliphoridae) larvae to convert food waste into valuable byproducts, while evaluating the antimicrobial properties of larval extracts. Under controlled laboratory conditions, the larvae reduced the weight of food waste by 21.87%, demonstrating their effectiveness in waste degradation. The optimal food waste-to-sawdust ratio was identified as 10:1. The bioconversion process resulted in 111.60-fold increase in larval biomass when reared on food waste and a 153.20-fold increase on fresh pork liver, highlighting their efficiency in converting protein-rich substrates. Larval extracts demonstrated significant antimicrobial activity against Bacillus subtilis and Pseudomonas aeruginosa, with minimum inhibitory concentrations (MICs) of 100 µg/ml. Proteomic analysis revealed proteins with potential antimicrobial and antioxidative properties. Furthermore, the extracts promoted cell growth in vitro without showing cytotoxic effects on HaCaT cell lines, suggesting potential applications in wound healing and infection control. These findings highlight the capacity of C. megacephala larvae to reduce food waste while generating antimicrobial agents, offering a sustainable approach to waste management with promising implications in medical applications.